How are Research for Development Programmes Implementing and Evaluatin g Equitable Partnerships to Address Power Asymmetries? - Snijder, Mieke; Steege, Rosie; Callander, Michelle; Wahome, Michel; Rahman, M. Feisal; Apgar, Marina; Theobald, Sally; Bracken, Louise J.; Dean, Laura; Mansaray, Bintu; Saligram, Prasanna; Garimella, Surekha; et al. (The European Journal of Development Research, 2023)
The complexity of issues addressed by research for development (R4D) r equires collaborations between partners from a range of disciplines an d cultural contexts. Power asymmetries within such partnerships may ob struct the fair distribution of resources, responsibilities and benefi ts across all partners. This paper presents a cross-case analysis of f ive R4D partnership evaluations, their methods and how they unearthed and addressed power asymmetries. It contributes to the field of R4D pa rtnership evaluations by detailing approaches and methods employed to evaluate these partnerships. Theory-based evaluations deepened underst andings of how equitable partnerships contribute to R4D generating imp act and centring the relational side of R4D. Participatory approaches that involved all partners in developing and evaluating partnership pr inciples ensured contextually appropriate definitions and a focus on w hat partners value.